The Relevance of Hassan Hanafi's Anthropocentric Theology Ideas towards the Re-Actualization of Islamic Thought in Indonesia - Syafieh, Syafieh; Katimin, Katimin; Sukiman, Sukiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study deals with the relevance of Hassan Hanafi's anthropocentric theology ideas towards the re-actualization of Islamic thought in Indonesia. The impact of Hassan Hanafi's anthropocentric theological thinking in Indonesia is less significant or even has no influence on the development of Islamic thought in Indonesia. In this case the researcher sees several reasons why the concept of anthropocentric theology Hassan Hanafi lacks a significant impact on the development of Islamic thought in Indonesia. First, the development of the anthropocentric theological thinking of Hassan Hanafi is too elitist. Second, Indonesian Muslims are still comfortable with the classical Asy'ariyah concept of theology. Third, the majority of Indonesian Muslims are still allergic to philosophy. The relevance and influence of Hassan Hanafi's thoughts began to appear around the 1993s, when several Hassan Hanafi books such as the Islamic Left (al-Yasa> r al-Islami) and offers of reconstructing classical Islamic theology from theocentric to anthropocentricity began to be translated and discussed by Indonesian Islamic experts. It can be concluded that The spirit of Indonesian Islamic intellectuals in studying and discussing the thoughts of Hassan Hanafi was not only carried out by reformers of Islamic Thought who already popular, but also carried out by young Islamic intellectuals who had a high enthusiasm to reform Islam in Indonesia.